Hip resurfacing arthroplasty versus large-diameter head metal-on-metal total hip arthroplasty: comparison of three Designs from the Finnish Arthroplasty Register. (March 2014) - Junnila, M.; Kostensalo, I.; Virolainen, P.; Remes, V.; Matilainen, M.; Vahlberg, T.; Pulkkinen, P.; Eskelinen, A.; Itälä, A.; Mäkelä, K.
Background and Aims: Large headed metal-on-metal total hip arthroplasty may produce more metal ions than hip resurfacing arthroplasty. Increased metal-ion levels may be associated with higher revision rates due to adverse reaction to metal debris. The purpose of our study was to compare the survivorship of three hip resurfacing arthroplasty designs with their analogous cementless large-diameter head metal-on-metal total hip arthroplasties. Material and Methods: Based on data obtained from the Finnish Arthroplasty Register, the revision risks of three metal-on-metal hip resurfacing arthroplasty/total hip arthroplasty design couples performed during 2001–2011 were analyzed using the Cox regression model. Results: In the Cox regression analysis for compared design pairs adjusted for age, gender, operated side, head size, diagnosis, and implant, there was no statistically significant difference in revision risk between ReCap hip resurfacing arthroplasty and Bimetric/ReCap total hip arthroplasty (risk ratio = 1.43, confidence interval = 0.95–2.14, p = 0.09) or between Birmingham hip resurfacing arthroplasty and Synergy/Birmingham hip resurfacing total hip arthroplasty (risk ratio = 1.35, confidence interval = 0.75–2.43, p = 0.31). However, the revision risk of Corail and Summit/articular surface replacement total hip arthroplasty (ASR HRA) was significantly increased compared to ASR HRA. (risk ratio = 0.73, confidence interval = 0.54–0.98, p = 0.04). Conclusion: We conclude that the short-term revision risk of large headed metal-on-metal total hip arthroplasties was not increased compared to analogous hip resurfacing arthroplasties in two out of three devices studied at a nationwide level. There may be implant-related factors having an effect on the success of single manufacturer devices. However, more information on the incidence of adverse soft-tissue reactions in these patient cohorts is needed.